Justice in the Distribution of Inheritance Rights for Indigenous Peoples - Radjawane, Pieter; Badaruddin, Wahdaniah (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Based on the law, inheritance is given to people who are related by marriage and blood relations, in customary law communities specifically in the western part of Seram, inheritance is given to adopted or returned children, known as dunale, and the children who come home get two parts, namely the part from the biological parents and the part from the adoptive parents. This causes problems in families who feel unfair in obtaining inheritance rights for certain children.Purposes of the Research: To analyze how an adopted child acquires an inheritance in order to provide justice for other children.Methods of the Research: The method used in this research is the empirical research method. This research was carried out using an empirical juridical approach which is a descriptive qualitative analysis study. The research attempts to describe the solution to the problem of Justice in the Distribution of Inheritance Rights for Adopted Children in Indigenous Communities in West Seram in the Abio Community, West Seram Regency.Findings of the Research: A home child or dunale is a child who is taken home as a legitimate child of the parents, even though the parents already have children or not, they will take home their grandchildren to be their children, whether from daughters or sons, and these children will receive inheritance rights from the parents who adopted them. Meanwhile, the child's family of origin no longer gets inheritance rights to maintain injustice in obtaining inheritance rights for other heirs from their original parents.